Evaluating Helminth to Treat Type 2 Diabetes – A Review - Made Dharmesti Wijaya; Anak Agung Gede Indraningrat (Warmadewa University, 2019)
Type 2 diabetes (T2D) is characterized by lacking production of insulin and impaired insulin sensitivity. Despite the availability of antidiabetic drugs on the market, exploration of new therapeutic drugs for treating T2D from nature remains necessary. This review provides insights on the potential of helminths and helminth derived products to modulate immune response for treating T2D. We discussed several helminths that are under investigation in animal models for treating T2D namely Schistosoma mansoni, Nippostrongylus brasiliens, Litomosoides sigmodontis, and Strongyloides stercoralis. Finally, application of Schistosoma mansoni soluble egg antigens (SEA) in T2D treatment is also examined.